The Power of Lyrics - Delwér, Dennis (My University, 2023)
Song lyrics have long served as a significant medium for artistic expression, offering valuable insights into the beliefs, emotions, and customs of diverse societies. With the advent of digital accessibility to music through online platforms, song lyrics have become even more accessible. This thesis aims to explore users’ behaviours and preferences regarding lyrics in a home context when using Spotify lyrics feature, uncovering underlying needs and objectives. The findings seek to inform enhancements to digital lyrics features and elevate the overall user experience. To ensure competitive edge and sustain user appeal, understanding the optimal utilisation of lyrics is crucial. Discerning the “when” and “how” of employing lyrics becomes pivotal in maintaining the platform’s allure and staying ahead of competitors. This was done through a series of methods that follow a classic user research design approach. Briefly, the main elements consisted of a literature study to understand the baseline conditions, followed by a recruitment process to find users for a digital diary study, followed by in-depth interviews. Insights were synthesised and later synthesised and organised in a framework. It consists of 15 proposed use cases, each with specific user needs based on seven identified core needs. Each use case was evaluated based on four different criteria, (1) Placement on the UX pyramid, (2) How well it maps to the intended area of interest of Spotify’s lyrics feature, (3) Potential to utilise the proposed capabilities of lyrics as artefacts and (4) Ability to utilise future trends in TV and Desktop. From the evaluation, the following three use cases were deemed to inhibit the greatest potential to increase the experience of digital lyrics in a home context. Learn & improve languages. The use case involves using the lyric feature on Spotify to learn and improve language skills through music, which offers a more accessible and enjoyable approach compared to traditional lan guage learning methods like books and films. Sing along with others. The use case involves users singing along with artists either alone or with others using Spotify’s lyrics feature, providing a “close enough” karaoke experience with live updating and synchronised lyrics. This activity is popular at social events and solo jam sessions. Create an ambiance. Users utilise the lyrics feature to curate personalised ambiances or moods, enhancing their experience by selecting songs with specific themes or atmospheres that suit their preferences. This use case satisfies the need for personal expression and identity, as well as the need for control and organisation over one’s environment
Keywords: Digital song lyrics, Lyrics as artefact, Use cases